Use of psychoactive substances during pregnancy and its harm to the neonate (Research, Society and Development, 2022)
The objective of this article is to describe what scientific production has published about the harm related to the use/abuse of psychoactive/psychotropic drugs in pregnant women and how this affects the formation or causes diseases to the newborn. The present study deals with a bibliographic research, this type of review is one of the methods used in Evidence-Based Practice (EBP). This practice allows the collection, categorization, evaluation and synthesis of the research results of the investigated topic, facilitating the use of the method. The search for samples resulted in a final number of 12 articles that were read and analyzed in full, there was a need to expand studies on the subject in the coming years, because even though the subject is current and important, articles were found in its predominance in 2019. The bibliography surveyed demonstrates the importance of the theme, since the consumption of alcohol, drugs and other psychoactive substances has increased considerably. The results presented allow us to infer that the use of licit and illicit drugs during pregnancy can have serious consequences for the newborn. In this sense, the elaboration of public policies and social assistance programs aimed at preventing this problem are fundamental in an attempt to reduce the harm caused by the abuse of these substances during the gestational period.